The standard of integral reparation in the jurisprudence of the Constitutional Court - Aguirre Castro, Pamela (2018)
This paper seeks to illustrate integral reparation effectiveness in ecuadorian constitutionalism. It begins with an analysis beyond the concept and scope of integral reparation provided in the constitutional norm. In a second moment, from the sociological-jurisprudential dimension, the paper treats integral reparation development in the judicial discourse that has been imposed by the Ecuadorian Constitutional Court in its binding decisions. As a consequence of this analysis, some reflections are proposed tending to contribute to integral reparation in judicial decisions.